2013
DOI: 10.1200/jop.2012.000698
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Hospitalization of Oncology Patients: Are We Missing an Opportunity for End-of-Life Care?

Abstract: Introduction: Despite advances in the care of patients with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
80
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 10 publications
4
80
0
Order By: Relevance
“…33 Additionally, for those oncology patients who were hospitalized, the mortality risk is well-known. 34 The current results may suggest a relationship between having cancer and having reduced serum levels of BDNF, although this association may be found due to potential confounding factors. The biology of the different types of cancer found in the patients enrolled in the study was diverse and might have impacted the result.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…33 Additionally, for those oncology patients who were hospitalized, the mortality risk is well-known. 34 The current results may suggest a relationship between having cancer and having reduced serum levels of BDNF, although this association may be found due to potential confounding factors. The biology of the different types of cancer found in the patients enrolled in the study was diverse and might have impacted the result.…”
Section: Discussionmentioning
confidence: 61%
“…An experimental model showed that acute stress induced a significant increase in BDNF mRNA and protein, while repeated chronic stress resulted in their reduction. 34 Therefore, we can hypothesize that chronic stress could be induced by cancer which, in turn, induced a reduction of BDNF. Furthermore, the small sample size is another factor that could explain the non-significance of BDNF levels between the oncology inpatients with delirium and those oncology inpatients without this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In our institution, most cancer-related admissions result from uncontrolled symptoms, are unplanned, and are associated with a median survival under four months. 1 Palliative care (PC) provides an extra layer of support alongside cancer care at any stage of disease. It This project was completed while Dr. Rocque focuses on identifying and meeting the patient's goals of care, including alleviation of physical, emotional, social, and spiritual suffering.…”
Section: Introductionmentioning
confidence: 99%
“…Inpatient stays present opportunities for palliative care consultations and discussions with the primary provider regarding goals of treatment [14]. The current study seeks to describe the utilization of invasive procedures on hospice patients referred from the inpatient setting in the 4 weeks prior to referral, and evaluate if these interventions have an overall positive or negative effect on several aspects of delivery of palliative care and their impact on overall survival.…”
Section: Introductionmentioning
confidence: 99%